Assessing temporomandibular disorders: mouthpiece design considerations - Buković, Dino; Glavičić, Igor; Dimitrić, Goran; Smajić, Miroslav; Radanović, Božana; Vitošević, Biljana (Vojnosanitetski pregled, 2020)
Background/Aim. Scuba diving is one of the sports with the fastest growing popularity. Nowadays doctors of dental medicine meet divers-patients in their offices more often. Treatment of these patients has some specific features that are related to difficulties in the temporomandibular joint, masticatory muscles and soft tissues of the oral cavity. A set of those complaints represent a condition called „diver’s mouth syndrome“. Most scuba divers complain of temporomandibular joint and the masticatory muscles pain; inadequate mouthpieces can exacerbate temporomandibular dysfunction (TMD) even when its symptoms are not present in everyday life. The aim of this research was to find a decent substitute for a fully customised mouthpiece, that are not present at our market, to discover the qualities of a good mouthpiece and establish prevalence of TMD among divers. Methods. This study included 30 scuba divers. Scuba divers filled out the questionnaire before diving, then dived twice with each of the 3 different commercial mouthpieces provided for this research (Mares Universal, Seac sub, Mares LiquidSkin (Universal Mares, Seac sub, Mares LiquidSkin). After diving, they filled out the second part of the questionnaire and so they performed an assessment of the mouthpiece and gave insight into the prevalence of TMD symptoms caused by using the mouthpiece. Results. According to the average score of satisfaction (the least present symptoms such as pain, fatigue, and numbness of the masticatory muscles and the jaw joint), this research proved Mares LiquidSkin mouthpieces to be the best out of the 3 commercial mouthpieces. For its use, average satisfaction score among participants was 7.07 (out of 10) and none of the divers reported jaw and muscle stiffness during and after the dive with this mouthpiece. The smallest percentage of participants reported pain in the orofacial region and discomfort while swallowing when used it in comparison with other mouthpieces. The anatomy and material of the mouthpieces turned out to be an extremely important factor. Conclusion. Several factors contribute to a good mouthpiece design; the choice of material, its elasticity and softness, the thickness and length of the interdental bite platform and the width of the oral screen that is inserted into the vestibule. The preferred material should be soft silicone. The interdental bite platforms should support the posterior teeth and the oral screen should fit the jaws and not be too wide.